Uncertainty in post-anaesthesia nursing clinical reasoning: An integrative review in the light of the model of uncertainty in complex health care settings - Cunha, Lara Daniela Matos (2022)
Problem identification: Post-anaesthesia nursing plays an important role in the early detection and treatment of clinical deterioration after surgery and/or anaesthesia. Concomitantly, the effectiveness of post-operative care is highly dependent on the accurate analysis, synthesis of patient data and quality of diagnostic decisions through clinical reasoning. Given the dynamic processes required to come to a diagnosis, uncertainty is common in clinical reasoning and expected during practice. Nevertheless, uncertainty may permeate the foundations of clinical reasoning, which can jeopardise diagnostic accuracy and consequently the quality and safety of health care. Literature search: The objectives of this review are to identify available evidence related to uncertainty in post-anaesthesia nursing clinical reasoning and to analyse the results from the perspective of the Model of Uncertainty in Complex Healthcare Settings (MUCH-S). A comprehensive search strategy using CINAHL (EBSCO), Cochrane Library (EBSCO), Medline (PubMed), ProQuest and Google Scholar databases was used to find published and unpublished relevant studies. Studies published in English and Portuguese were included. There was no temporal restriction, nor geographical or cultural limitation for the studies included. Data evaluation synthesis: All papers were reviewed by the authors to extract key information about purpose, sample and setting, research design and method, key findings and limitations. The literature search identified a total of 248 studies, 22 of which were retrieved for full reading. A total of four articles were included in this review. Implications for practice: Three main themes were identified: nurses’ intuition to reason, feelings of uncertainty related to lack of nursing knowledge and clinical (in)experience to deal with uncertainty. These findings are encompassed within the MUCH-S taxonomy: personal, scientific and practical. This review offers post-anaesthesia nurses’ greater levels of understanding of this phenomenon and may support more informed and reflexive clinical reasoning.